Fertility-sparing treatment for patients with endometrial cancer: a bibliometric analysis from 2000 to 2024 - Gao, Yue; Wang, Huali; Jiang, Meng; Cui, Yumeng; Yu, Xiaochuan (Frontiers in Oncology, 2025)
IntroductionThe rising global incidence of endometrial cancer (EC), particularly among younger patients, has established fertility-sparing treatment as a critical focus in gynecological and reproductive medicine. Despite its clinical significance, comprehensive bibliometric analyses in this field remain limited.MethodsThis study conducted the most extensive bibliometric analysis to date, encompassing 506 publications on fertility-sparing EC treatments published between January 1, 2000, and December 22, 2024. Utilizing CiteSpace, JepaC, and VOSviewer, we systematically evaluated contributions across regions, institutions, journals, authors, and keywords to identify emerging research trends.ResultsChina and the United States emerged as leading contributors, collectively accounting for 44.3% of publications. Fudan University and Cha University were identified as the most active institutions. Author Chen Xiaojun demonstrated the highest publication output, while Seok J and Seong SJ ranked as the most frequently cited researchers. Keyword analysis revealed five dominant research themes: "progestin," "reproductive outcomes," "age," "prognostic factors," and "myometrial invasion."DiscussionThis analysis delineates the evolving landscape of fertility-sparing EC research, highlighting persistent emphasis on hormonal therapies and prognostic determinants. The findings underscore the need for standardized treatment protocols and long-term fertility outcome studies. By mapping research trajectories and visualizing knowledge networks, this study provides actionable insights to guide future investigations in reproductive oncology.